Conservation priority corridors enhance the effectiveness of protected area networks in China - Weicheng Sun; Entao Zhang; Yujin Zhao; Zhisheng Wu; Wenhe Chen; Yao Wang; Yongfei Bai (Communications Earth & Environment)
Abstract The expansion and interconnection of protected areas are central to achieving the Kunming-Montreal Global Biodiversity Framework’s ambitious goals, yet their synergistic relationship remains underexplored. Here, we propose a framework integrating wildlife dispersal-based connectivity to address two key objectives in China: (1) constructing a cost-effective nature conservation network by combining connectivity and biodiversity prioritization, and (2) evaluating climate and anthropogenic risks while addressing habitat representation gaps. The framework aims to designate 30% of land as protected areas and informally allocate additional 30% of land as conservation priority corridors. Results show this strategy connects 57% of existing protected areas, protects 74% of priority zones, and achieves 89% of habitat representation targets. While current protected areas mitigate climate and anthropogenic threats, future expansion faces challenges due to geographic variations in these threats and the necessity for adequate representation. Our approach identifies and prioritizes these challenges, offering a data-driven pathway to achieve Kunming-Montreal targets.